Viability of barley seeds by the tetrazolium test - Grzybowski,Camila Ribeiro de Souza (2012)
The tetrazolium test is used to control seed quality of various plant species since it allows a rapid evaluation of viability. Freshly harvested barley seeds show dormancy that can make the germination test ineffective for an immediate evaluation. Therefore, the development of more efficient methods, such as the tetrazolium test, is necessary. The objective of this research work was to study various procedures for performing the tetrazolium test on barley seeds. Five lots of cv. BRS 195 barley seeds were used and subjected to the following treatments: two different methods of seed preconditioning (direct immersion in H2O and between sheets of moistened paper towels); two types of preparation for staining (longitudinal cross-section of the seed through the embryo with immersion of one half in a 2,3,5 triphenyl tetrazolium chloride solution or placing both halves on top of filter paper moistened with the tetrazolium salt solution); two methods of staining (on top of filter paper and direct immersion in the tetrazolium salt solution). Three concentrations of the tetrazolium salt solution (0.1%, 0.5%, and 1.0%) were used. It was concluded that the tetrazolium test on barley seeds may be accomplished with preconditioning by direct immersion in H2O and staining by immersing in a 0.1% or 0.5% concentration of tetrazolium salt solution or staining on top of filter paper moistened with such solution at a 1.0% concentration.